Celiac disease and risk of microscopic colitis: A nationwide population‐based matched cohort study. Issue 2 (20th March 2023) - Bergman, David; Khalili, Hamed; Lebwohl, Benjamin; Roelstraete, Bjorn; Green, Peter H. R.; Ludvigsson, Jonas F.
Abstract: Background: An association has been reported between celiac disease (CD) and microscopic colitis (MC). However, large, population‐based cohort studies are rare. Objective: To systematically examine the association between CD and MC in a large, nationwide cohort. Methods: We conducted a nationwide population‐based matched cohort study in Sweden of 45, 138 patients with biopsy‐verified CD (diagnosed in 1990–2016), 223, 149 reference individuals, and 51, 449 siblings of CD patients. Data on CD and MC were obtained from all ( n  = 28) pathology departments in Sweden. Adjusted hazard ratios (aHRs) were calculated using Cox regression. Results: During follow‐up, 452 CD patients and 197 reference individuals received an MC diagnosis (86.1 vs. 7.5 per 100, 000 person‐years). This difference corresponded to an aHR of 11.6 (95% confidence interval [CI] = 9.8–13.8) or eight extra MC cases in 1000 CD patients followed up for 10 years. Although the risk of MC was highest during the first year of follow‐up (aHR 35.2; 95% CI = 20.1–61.6), it remained elevated even after 10 years (aHR 8.1; 95% CI = 6.0–10.9). Examining MC subtypes lymphocytic colitis (LC) and collagenous colitis (CC) separately, the aHR was 12.4 (95% CI = 10.0–15.3) for LC and 10.2 (95% CI = 7.7–13.6) for CC. MC was also more common before CD (adjusted odds ratio [aOR] = 52.7; 95% CI = 31.4–88.4). Compared to siblings, risk estimates decreased but remained elevated (CD and later MC: HR = 6.2; CD and earlier MC: aOR = 7.9). Conclusion: Our study demonstrated a very strong association of MC with CD with an increased risk of future and previous MC in CD patients. The magnitude of the associations underscores the need to consider the concomitance of these diagnoses in cases in which gastrointestinal symptoms persist or recur despite a gluten‐free diet or conventional MC treatment. The comparatively lower risk estimates in sibling comparisons suggest that shared genetic and early environmental factors may contribute to the association between CD and MC. Abstract :